Catalytic Oxidative Desulfurization of Dibenzothiophene by Composites Based Ni/Al-Oxide - Nur Ahmad; Alfan Wijaya; Amri; Erni Salasia Fitri; Fitri Suryani Arsyad; Risfidian Mohadi; Aldes Lesbani (Science and Technology Indonesia, 2022)
In the present study, composite layer double hydroxide-metal oxide (Ni/Al-TiO2 and Ni/Al-ZnO) was successfully prepared and used as catalyst of oxidative desulfurization of dibenzothiophene. Characterization of catalyst was used XRD, FTIR, and SEM-EDS. The structure of Ni/Al-LDH, TiO2, and ZnO in composite Ni/Al-TiO2 and Ni/Al-ZnO was consistent, which also indicated that the preparation of composite did not change the form of precursors. FTIR spectra of Ni/Al-TiO2 and Ni/Al-ZnO absorption band at 3398, 1639, 1339, 832, 731, and 682 cm−1. The catalysts have an irregular structure, TiO2 and ZnO adhere to the surface of Ni/Al LDH. The percent mass of Ti and Zn on the composite at 29.3% and 18.2%, respectively. The acidity of Ni/Al LDH increased after being composited with TiO2 and ZnO. The optimum reaction time, dosage catalyst, and temperature were 30 min, 0.25 g, and 50°C, respectively, and n-hexane as a solvent. The percentage conversion of dibenzothiophene on Ni/Al-LDH, TiO2, ZnO, Ni/Al-TiO2, and Ni/Al-ZnO were 99.44%, 91.92%, 95.36%, 99.88%, and 99.90%, respectively. The catalysts are heterogeneous system and the advantage is that can be used for reusability. After 3 times catalytic reactions, the conversion of dibenzothiophene still retains more than 80%, even Ni/Al-TiO2 and Ni/Al-ZnO composites still 97.79% and 98.99%, respectively.